2022
DOI: 10.1186/s13023-022-02453-z
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 in Leber hereditary optic neuropathy mutation carriers: a prospective cohort study

Abstract: Background Leber hereditary optic neuropathy (LHON) is the most common mitochondrial disorder, frequently resulting in acute or subacute severe bilateral central vision loss. Vitamin B12 deficiency is also a known cause of optic neuropathy through mitochondrial dysfunction. Here we evaluated the prevalence and clinical significance of vitamin B12 deficiency in a large cohort of LHON patients and asymptomatic mutation carriers from a tertiary referral center. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Vitamin B12 deficiency has been identified amongst etiologies of unilateral optic atrophy with contralateral disc edema without cranial space-occupying lesions (pseudo-Foster Kennedy syndrome) [ 297 , 298 , 299 ]. High rates of vitamin B12 deficiency have been reported among carriers of Leber’s hereditary optic neuropathy [ 300 ].…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin B12 deficiency has been identified amongst etiologies of unilateral optic atrophy with contralateral disc edema without cranial space-occupying lesions (pseudo-Foster Kennedy syndrome) [ 297 , 298 , 299 ]. High rates of vitamin B12 deficiency have been reported among carriers of Leber’s hereditary optic neuropathy [ 300 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies revealed deficiencies in vitamin B12 [ 52 ] or in both taurine and vitamin B3 (nicotinamide) [ 53 ] in LHON patients. It has been proposed that vitamin B12 levels should be monitored regularly or, if necessary, corrected in LHON carriers [ 52 ].…”
Section: Environmental Protective Factorsmentioning
confidence: 99%
“…Leber's hereditary optic neuropathy (LHON) is a relatively rare disease compared to glaucoma, but it is considered the most frequent mitochondrial DNA (mtDNA) disorder [323]. It follows a maternal inheritance pattern and primarily affects young males, typically presenting between the ages of 15 and 35 [32].…”
Section: Leber's Hereditary Optic Neuropathy 431 General Aspects: Gen...mentioning
confidence: 99%
“…Other studies have explored potential factors that may explain the incomplete penetrance and have found that smoking and excessive alcohol consumption are more common in individuals with LHON compared to asymptomatic carriers [334]. Additionally, it has been suggested that vitamin B12 (cobalamin) deficiency could accelerate the symptomatology in LHON carriers [335], and that regular screening for vitamin B12 levels may be considered in LHON carriers and patients [323].…”
Section: Leber's Hereditary Optic Neuropathy 431 General Aspects: Gen...mentioning
confidence: 99%